Dynamism of Sports Diplomacy and Foreign Policy as Correlate of Sports Development in North-Central State, Nigeria - Falaye, Elijah Kayode; Fayomi, Oluwafemi (Indonesian Journal of Sport Management, 2023)
The central focus of this study was to articulate a better image of Nigeria's sports diplomacy and foreign policy on the development of sports in North – Central state Nigeria. A descriptive research design of survey types was employed for this study. The population for this study comprises all sports administration in the study. A purposive sampling technique was used to select 588 respondents for the study. A researcher-structured questionnaire was used to gather information from the respondents. Three experts validated the instrument and tested for reliability through the test re-test method using Pearson Product Moment Correlation. A correlation coefficient of 0.75" r' was obtained. The researchers administered the instrument, and the data collected were analyzed using inferential statistics of Pearson Product Moment Correlations (PPMC) to test the formulated hypotheses set for the study at 0.05 alpha level. The finding revealed a significant relationship between politics in sports and sports development. Also, there was a significant relationship between management practice and sports development in North-Central State Nigeria. Based on the study's findings, it was recommended that politics in sports should not be allowed to discourage the private sector from sponsoring sports programmes that can bring about sports development in society. Also, sports administrators are encouraged to adopt best management practices that would bring about sports development.